High-flux and high-precision ceramic flat sheet membrane for removing iron fishy smell of drinking tap water and preparation method of high-flux and high-precision ceramic flat sheet membrane

By introducing zeolite molecular sieve and high boron ultrafine glass powder into the ceramic plate film, high-precision ceramic plate film is prepared, which solves the problem of difficulty in removing the iron smell of drinking tap water in the prior art, and achieves an efficient and economical iron smell removal effect.

CN119607898APending Publication Date: 2025-03-14JIANGSU PROVINCE YIXING NONMETALLIC CHEM MACHINERY FACTORY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411915672.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove the fishy iron smell in drinking tap water, and the commonly used iron removal methods are costly and have a great impact on water quality.

Method used

A high-throughput high-precision ceramic flat film is used. By introducing the MFI topological structure ZSM-5 type zeolite molecular sieve into the ceramic flat film support as an adsorbent, and combining high-boron ultrafine glass powder for ultra-fine glass powder for ultra-low temperature sintering, a high-precision filter layer and adsorption layer are prepared. The ceramic flat film is integrated using the principle of molecular sieve to enhance the adsorption capacity.

Benefits of technology

It has achieved efficient removal of the iron smell in drinking tap water, and the adsorption removal rate of rust impurities is as high as more than 99%, while reducing the operating cost of split filtration, ensuring the quality of water effluent and water safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a large-flux high-precision ceramic flat sheet membrane for removing iron and fishy smell of drinking tap water and a preparation method thereof, and belongs to the technical field of ceramic flat sheet membranes. The ceramic flat sheet membrane comprises a support body, a high-precision filter layer, an adsorption layer and a filling adsorbent. The preparation method comprises the following steps: 1) preparing a ceramic flat sheet membrane mud green body; (2) preparing a ceramic flat sheet membrane support body; 3) preparing a high-precision filter layer by a dip-coating method; (4) preparing an adsorption layer by a spraying method; and (5) filling a reinforced adsorbent and packaging an end. According to the present invention, the ultra-fine membrane material is used to produce the high separation precision, the effluent quality is ensured, the operation cost of the split type filtration is reduced, the molecular sieve adsorption membrane and the enhanced filling adsorbent are produced, and the iron ions in the urban tap water are effectively adsorbed; the vacuum dip-coating method is matched with the one-time sintering process, so that the working procedures can be saved, the yield is high, the membrane layer thickness and the membrane surface are uniform and consistent, basically no pore defect exists, and the flux and the precision stability of the ceramic flat membrane product are further stabilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic flat membranes, and more specifically, relates to a high-flux, high-precision ceramic flat membrane for removing the iron smell of drinking tap water and a preparation method thereof. Background Art

[0002] The "new national standard" of "Sanitary Standard for Drinking Water" (GB5749-2022) was officially implemented on April 1, 2023. Compared with the original standard, the new standard has the following changes: more attention is paid to the sensory indicators of drinking water taste, such as color, turbidity, odor and taste. In recent years, due to water pollution, specific environmental influences have caused the odor and taste in drinking water to exceed the standard, affecting water quality safety and residents' water comfort.

[0003] The state stipulates that the iron content in drinking water is over the standard if it is >0.5mg / L for small centralized water supply and decentralized water supply, and over the standard if it is >0.3mg / L for regular drinking water. In addition, the iron ion content should be ≤0.3mg / L. When the iron content in water is >0.3mg / L, the water becomes turbid. When it exceeds 1 mg / L, the water has a distinct iron smell. There are several main forms of iron in water: granular iron oxide, ferric iron colloid, and divalent iron ions. Although the state has not set a separate standard for ferric iron, the iron smell in water is mainly caused by rust containing ferric iron.

[0004] With the acceleration of industrialization, the metal parts of tap water pipes will gradually age and corrode over time after being used for a period of time. The iron smell in tap water comes from the iron ions released after the iron pipes are corroded, and the high-rise water supply reserve tanks are difficult to clean after long-term use, resulting in the precipitation of impurities such as iron. Rust pollution has become the biggest danger to people in tap water pollution. After long-term drinking, the human body may accumulate excessive iron elements, causing chronic over-poisoning.

[0005] At present, most of the iron removal methods used in China are RO reverse osmosis membranes, but the cost of use is high, and the water filtered by RO reverse osmosis membranes is extremely clean, while removing the minerals needed by the human body, which is not good for health. On ultrafiltration membranes, inorganic alumina and zirconium oxide interception molecular membranes are currently mostly used, which can remove some iron impurities, but cannot completely remove iron ions. They need to be adsorbed by the subsequent organic activated carbon process, which increases the filtration and adsorption process, and increases the floor space and maintenance costs. Summary of the invention

[0006] In view of the above-mentioned problems existing in the prior art, the technical problem to be solved by the present invention is to provide a high-precision ceramic flat membrane with a large flux for removing the iron smell of drinking tap water and a preparation method thereof. While ensuring the filtration efficiency at a large flux, high-precision separation accuracy is produced by using ultrafine membrane materials to ensure the water quality. At the same time, the molecular sieve principle is integrated with the ceramic flat membrane, which greatly reduces the operating cost of the split filtration. A molecular sieve adsorption membrane and an enhanced filling adsorbent are produced. While the high-precision filtration membrane intercepts part of the iron impurities, it can effectively adsorb the iron ions in the city tap water.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A high-throughput, high-precision ceramic flat membrane for removing the iron odor of drinking tap water, comprising a support, a high-precision filter layer, an adsorption layer and a filling adsorbent;

[0009] The support comprises the following raw materials and their weight proportions: 20-50 parts of silicon carbide, 15-20 parts of prefabricated 1# zeolite, 2-5 parts of high-boron ultrafine glass powder, 3-6 parts of kaolin, 4-8 parts of PP balls, 5-12 parts of hydroxypropyl methylcellulose, 4-6 parts of tung oil, 3-6 parts of polyvinyl alcohol aqueous solution, and 12-18 parts of water;

[0010] The high-precision filter layer includes the following raw materials and their weight fractions: 40-46 parts of titanium dioxide, 0.02-0.1 parts of polyacrylamide, 1-3 parts of anhydrous ethanol, 5-10 parts of polyacrylic acid, 7-18 parts of polyvinyl alcohol aqueous solution, and 25-40 parts of water;

[0011] The adsorption layer comprises the following raw materials and their weight proportions: 30-55 parts of prefabricated 2# zeolite, 3-5 parts of anhydrous ethanol, 5-10 parts of sodium carboxymethyl cellulose, 3-6 parts of hydroxypropyl methyl cellulose, 5-12 parts of polyvinyl alcohol aqueous solution, and 20-35 parts of water;

[0012] The filling adsorbent includes the following raw materials and their mass proportions: 45-55 parts of 3# zeolite and 45-55 parts of activated carbon powder.

[0013] A method for preparing the high-flux, high-precision ceramic flat membrane for removing the iron smell of drinking tap water comprises the following steps:

[0014] 1) Preparation of ceramic flat membrane mud body:

[0015] After a certain ratio of silicon carbide, prefabricated 1# zeolite, ultrafine glass powder and kaolin are mixed at high speed, hydroxypropyl methylcellulose, tung oil, polyvinyl alcohol aqueous solution and water are added and mixed evenly, and finally pore-forming agent PP balls are added and mixed evenly at a slow speed, after the mixing is completed, the mixture is added to a mud kneading machine for mud kneading, and after the mud kneading, the mixture is placed in an aging box for aging, and after aging, it is extruded and formed into a ceramic flat membrane mud body;

[0016] 2) Preparation of ceramic flat membrane support;

[0017] 3) Preparation of high-precision filter layer by dip coating:

[0018] The ceramic flat membrane support body is clamped at both ends with a clamp, with the side as the upper and lower sides, and is evenly immersed and suspended in the high-precision filter layer slurry, and vacuum -0.04~-0.06MPa adsorption is performed, the adsorption time is 5~10s, and the adsorption thickness is 100~180μm. After drying, it is sintered at 650~750℃ to obtain a ceramic flat membrane containing a high-precision filter layer;

[0019] 4) Preparation of adsorption layer by spraying method:

[0020] The adsorption layer slurry is uniformly sprayed on the surface of the ceramic flat membrane containing the high-precision filtration layer with a thickness of 200-500 μm, and then quickly dried at 80-90°C, and then sintered at 350-500°C to obtain the ceramic flat membrane containing the adsorption layer;

[0021] 5) Filling and strengthening adsorbent and end packaging.

[0022] Preferably, the preparation process of the prefabricated 1# zeolite is as follows: hydroxypropyl methylcellulose and water are prepared into an aqueous solution in a mass ratio of 1:30, 1# zeolite is added and stirred for 2-4 hours, and the pores on the surface of the zeolite particles completely adsorb the hydroxypropyl methylcellulose aqueous solution, and then spray-dried and granulated at 110°C to obtain the prefabricated 1# zeolite.

[0023] Preferably, in step 2), the process of preparing the ceramic flat membrane support body is: subjecting the formed ceramic flat membrane mud body to natural moisturizing drying for 48 to 55 hours, and then subjecting the body to heating radiation drying at a temperature of 60 to 90°C for a drying time of 4 to 15 hours. After drying the body, it is sintered to obtain the ceramic flat membrane support body.

[0024] Preferably, the specific sintering process of the dried green body is: heating the dried green body from 30°C to 400°C at a rate of 60°C / h, then heating it to 800-850°C at a rate of 100°C / h, and keeping it warm for 1-3.5h.

[0025] Preferably, in step 3), the preparation process of the high-precision filter layer is: titanium dioxide, polyacrylamide, anhydrous ethanol, polyacrylic acid, polyvinyl alcohol aqueous solution, and water are added to a ball mill and mixed for 7 to 15 hours, ultrasonically treated for 1 to 2 hours, and then added to a ball mill and mixed for 1 to 3 hours to obtain a high-precision filter layer slurry.

[0026] Preferably, in step 3), the specific process of sintering the high-precision filter layer is as follows: the temperature is increased from 30°C to 300°C at a rate of 30°C / h; then the temperature is increased to 650-750°C at a rate of 60°C / h, and sintered for 1-2 hours to obtain a ceramic flat membrane containing a high-precision filter layer.

[0027] Preferably, in step 4), the preparation steps of the adsorption layer slurry are as follows:

[0028] (1) After preparing an aqueous solution of hydroxypropyl methylcellulose and water in a mass ratio of 1:30, add 2# zeolite and stir and soak for 2-4 hours. After the pores on the surface of the zeolite particles completely adsorb the hydroxypropyl methylcellulose aqueous solution, spray dry and granulate at 110°C to obtain prefabricated 2# zeolite;

[0029] (2) Prefabricated 2# zeolite, anhydrous ethanol, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl alcohol aqueous solution and water are mixed, added into a planetary ball mill and mixed for 1 to 2 hours, and then centrifuged and dispersed for 30 to 60 minutes to obtain an adsorption layer slurry.

[0030] Preferably, in step 4), the specific process of sintering is: heating the dried ceramic flat membrane containing the adsorption layer from 30°C to 120°C at a rate of 30°C / h, then heating to 350-500°C at a rate of 120°C / h, and keeping the temperature for 1-3h.

[0031] Preferably, in step 5), filling the enhanced adsorbent and the end cap packaging specifically include the following steps:

[0032] S1. One end of the ceramic flat membrane containing the adsorption layer is sealed with an ABS strip using epoxy resin, and then naturally dried and cured for 24 hours;

[0033] S2. The opening of the single-head packaged ceramic flat membrane is vertically facing upward, and 3# zeolite and activated carbon powder particles are filled into the pores of the flat membrane, and vibrated to fill them as enhanced filling adsorbents;

[0034] S3.: According to step S1, encapsulate the other end of the ABS strip, dry and cure naturally for 24 hours, and finally obtain a high-flux and high-precision ceramic flat membrane.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1) The present invention introduces MFI topological structure ZSM-5 zeolite molecular sieve as an adsorbent in the ceramic flat membrane support body formula, selects its high temperature stability and high activity, and uses high-boron ultrafine glass powder as the main sintering aid for ultra-low temperature sintering to obtain a support body with a certain strength while effectively maintaining the adsorption activity of the zeolite, so that the capillaries in the two pore structures can be used to exert a good adsorption effect in the later stage;

[0037] 2) The present invention performs organic pre-sealing and curing treatment on the zeolite molecular sieve to prevent the adsorption of fine inorganic powder to form pore blockage during the mixing process, and after the molding and drying, the organic binder adsorbed on the capillary pores and surface is naturally discharged after sintering, the natural capillary pores are restored, the specific surface area of ​​the molecular sieve zeolite is restored, and its effective adsorption effect is maximized;

[0038] 3) The present invention not only selects fine particles as the support skeleton of the ceramic flat membrane, but also uses a layer of ultrafine particle titanium oxide membrane to ensure high flux in engineering applications while maintaining interception accuracy, thus playing a role in initially intercepting iron impurities in tap water;

[0039] 4) The present invention uses the SBA-15 mesoporous zeolite molecular sieve with the best adsorption effect as a supplementary adsorption layer on the surface of the high-precision filtration membrane, and utilizes its hydrothermal stability, large specific surface area and uniform pore characteristics, which is conducive to its stable use in the hydrothermal system, and further enhances the adsorption and removal rate of rust impurities and iron ions in the working conditions of the product;

[0040] 5) The present invention further enhances the adsorption of rust impurities and iron ions that escape after adsorption by the adsorption layer and the support layer by filling zeolite and activated carbon in the pores of the ceramic flat membrane support, so that the adsorption removal rate of rust impurities is as high as more than 99%;

[0041] 6) The present invention uses a vacuum dip coating method combined with a one-time sintering process, which can save steps, have a high yield rate, uniform membrane thickness and membrane surface, and basically no pore defects, further stabilizing the flux and precision stability of ceramic flat membrane products;

[0042] 7) The ceramic flat membrane prepared by the present invention ensures filtration efficiency at a large flux and at the same time, uses ultrafine membrane materials to make high-precision filtration separation membranes to ensure water quality. It also uses the principle of zeolite molecular sieves to integrate organic adsorbents, inorganic adsorbents and ceramic flat membranes, which greatly reduces the operating cost of split-type filtration. It also produces molecular sieve adsorption membranes and enhanced filling adsorbents, which can effectively adsorb heavy metal ions in urban tap water, especially the iron smell caused by trivalent iron ions, which is a nuisance to people, and ensures the long-term safety of water use. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following examples, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0044] In the following examples, the raw material specifications used are shown in Table 1 below:

[0045] Table 1 Specifications of raw materials used

[0046]

[0047] Example 1

[0048] A method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron smell of drinking tap water comprises the following steps:

[0049] 1. Preparation of Ceramic Flat Membrane Mud Body

[0050] (1) Pretreatment of 1# zeolite: 6 parts of hydroxypropyl methylcellulose and water are mixed into an aqueous solution at a mass ratio of 1:30, and then 60 parts of 1# zeolite are added and stirred for 3 hours. After the pores on the surface of the 1# zeolite particles completely adsorb the hydroxypropyl methylcellulose aqueous solution, the granulation is spray-dried at 110°C to obtain prefabricated 1# zeolite for standby use;

[0051] (2) 35 parts of silicon carbide, 15 parts of prefabricated dried 1# zeolite, 5 parts of high-boron ultrafine glass powder, and 5 parts of kaolin were added to the Elysee high-speed mixer for premixing at 1000 r / min for 15 minutes, and then 10 parts of hydroxypropyl methyl fiber, 5 parts of tung oil, 5 parts of polyvinyl alcohol aqueous solution, and 15 parts of water were added and mixed for 20 minutes. Finally, 5 parts of pore-forming agent PP hollow balls were added and mixed at 600 r / min for 10 minutes. After mixing, the mixture was added to the mud kneading machine for vacuum-0.085 MPa mud kneading. After mud kneading, the mixture was placed in an aging box for aging at a temperature of 24~28°C and a humidity of 80~85%. After aging, the mixture was extruded at a vacuum of -0.090 MPa and a pressure of 6.2~6.7 MPa to obtain a ceramic flat membrane mud body;

[0052] 2. Preparation of ceramic flat membrane support

[0053] (1) Drying of the ceramic flat membrane mud body: The formed ceramic flat membrane mud body is naturally dried for 55 hours, and then subjected to heating radiation drying at a temperature of 60°C for 4 hours; then the temperature is raised to 80°C for 6 hours to obtain a dry body with a water loss rate of ≥95%;

[0054] (2) Sintering the dried ceramic flat membrane mud body: heating the dried body from 30°C to 400°C at a rate of 60°C / h; then heating the body to 820°C at a rate of 100°C / h, and sintering the body for 3 hours to obtain a ceramic flat membrane support body;

[0055] 3. Preparation of high-precision filter layer by dip coating

[0056] (1) 46 parts of titanium dioxide, 0.1 parts of polyacrylamide, 3 parts of anhydrous ethanol, 8 parts of polyacrylic acid, 13 parts of polyvinyl alcohol aqueous solution, and 29.9 parts of water were added to a ball mill and mixed for 12 hours, then ultrasonically treated for 2 hours, and added to a ball mill and mixed for 3 hours to form a suspended high-precision filter layer slurry;

[0057] (2) Clamp the two ends of the ceramic flat membrane support with a clamp, immerse it evenly in the suspended high-precision filter layer slurry with the side as the upper and lower surfaces, and use a vacuum of -0.06MPa to adsorb the upper membrane for 10s. The adsorption thickness is 150~180μm. After the high-precision filter layer is dried at 40℃ for 8h, a ceramic flat membrane support containing a high-precision filter layer with a water loss rate of ≥96% is obtained.

[0058] (3) The ceramic flat membrane support body containing the high-precision filtration layer was heated from 30°C to 300°C at a rate of 30°C / h; then raised to 750°C at a rate of 60°C / h, and sintered for 2 hours to obtain a ceramic flat membrane containing the high-precision filtration layer.

[0059] 4. Preparation of adsorption layer by spraying

[0060] (1) Pretreatment of 2# zeolite: 6 parts of hydroxypropyl methylcellulose and water are mixed into an aqueous solution at a mass ratio of 1:30, and then 60 parts of 2# zeolite are added and stirred for 3 hours. After the pores on the surface of the 2# zeolite particles completely adsorb the hydroxypropyl methylcellulose aqueous solution, the mixture is spray-dried and granulated at 110°C to obtain prefabricated dry 2# zeolite for standby use;

[0061] (2) 40 parts of prefabricated dried 2# zeolite, 5 parts of anhydrous ethanol, 9 parts of sodium carboxymethyl cellulose, 4 parts of hydroxypropyl methylcellulose, 7 parts of polyvinyl alcohol aqueous solution and 35 parts of water were mixed, added into a planetary ball mill and mixed for 2 hours, and centrifuged for 60 minutes to obtain an adsorption layer slurry;

[0062] (3) The adsorption layer slurry is uniformly sprayed on the surface of the high-precision filtration layer of the flat membrane at a positive pressure of 0.03 MPa, with a spraying thickness of about 400-500 μm. It is then rapidly radiated and dried at 90°C until the water loss rate is ≥96%. The temperature is then increased from 30°C to 120°C at a rate of 30°C / h; the temperature is then increased to 450°C at a rate of 120°C / h, and the temperature is kept at this temperature for 2 hours before sintering to obtain a ceramic flat membrane containing an adsorption layer.

[0063] 5. Filling and strengthening adsorbent and end packaging

[0064] (1) Single-end ABS strip packaging: Use epoxy resin to seal one end of the ceramic flat membrane containing the adsorption layer with an ABS strip, and then naturally dry and solidify it for 24 hours;

[0065] (2) Filling method: Place the single-head packaged flat membrane with the opening facing upwards, and fill 50 parts of 3# zeolite and 50 parts of activated carbon powder particles into the pores of the flat membrane. Vibrate and fill appropriately to enhance the filling of the adsorbent.

[0066] (3) Encapsulating the other end with ABS rubber strip: According to the above step (2), seal the end with BS rubber strip. After natural drying and curing for 24 hours, a high-flux and high-precision ceramic flat membrane product is obtained.

[0067] Example 2

[0068] A method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron smell of drinking tap water comprises the following steps:

[0069] 1. Preparation of Ceramic Flat Membrane Mud Body

[0070] (1) Pretreatment of 1# zeolite: 6 parts of hydroxypropyl methylcellulose and water are mixed into an aqueous solution at a mass ratio of 1:30, and then 60 parts of 1# zeolite are added and stirred for 3 hours. After the pores on the surface of the 1# zeolite particles completely adsorb the hydroxypropyl methylcellulose aqueous solution, the granulation is spray-dried at 110°C to obtain prefabricated 1# zeolite for standby use;

[0071] (2) 20 parts of silicon carbide, 20 parts of prefabricated 1# zeolite, 4 parts of high-boron ultrafine glass powder, and 6 parts of kaolin were added to the Elysee high-speed mixer for premixing at 1000 r / min for 15 minutes, 12 parts of hydroxypropyl methyl fiber, 6 parts of tung oil, 6 parts of polyvinyl alcohol aqueous solution, and 18 parts of water were added and mixed for 20 minutes, and finally 8 parts of pore-forming agent PP hollow balls were added and mixed at 600 r / min for 10 minutes. After mixing, the mixture was added to the mud kneading machine for vacuum-0.085 MPa mud kneading. After mud kneading, the mixture was placed in an aging box for aging at a temperature of 24~28°C and a humidity of 80~85%. After aging, the mixture was extruded at a vacuum of -0.090 MPa and a pressure of 6.2~6.7 MPa to obtain a ceramic flat membrane mud body;

[0072] 2. Preparation of ceramic flat membrane support

[0073] (1) Drying of the ceramic flat membrane mud body: The formed ceramic flat membrane mud body is naturally moisturized and dried for 55 hours, and then subjected to heating radiation drying at a temperature of 60°C for 4 hours; then the temperature is raised to 80°C for 6 hours to obtain a dry body with a water loss rate ≥ 95%;

[0074] (2) Sintering the dried ceramic flat membrane mud body: heating the dried body from 30°C to 400°C at a rate of 60°C / h; then heating the body to 820°C at a rate of 100°C / h, and sintering the body for 3 hours to obtain a ceramic flat membrane support body;

[0075] 3. Preparation of high-precision filter layer by dip coating

[0076] (1) 46 parts of titanium dioxide, 0.1 parts of polyacrylamide, 3 parts of anhydrous ethanol, 8 parts of polyacrylic acid, 13 parts of polyvinyl alcohol aqueous solution, and 29.9 parts of water were added to a ball mill and mixed for 12 hours, then ultrasonically treated for 2 hours, and added to a ball mill and mixed for 3 hours to form a suspended high-precision filter layer slurry;

[0077] (2) Clamp the two ends of the ceramic flat membrane support with a clamp, immerse it evenly in the suspended high-precision filter layer slurry with the side as the upper and lower sides, and use vacuum -0.06MPa to adsorb the upper membrane for 10s, with an adsorption thickness of 150~180μm. After drying the high-precision separation layer at 40℃ for 8h, a ceramic flat membrane support containing a high-precision filter layer with a water loss rate of ≥96% is obtained;

[0078] (3) The ceramic flat membrane support body containing the high-precision filtration layer was heated from 30°C to 300°C at a rate of 30°C / h; then raised to 750°C at a rate of 60°C / h, and sintered for 2 hours to obtain a ceramic flat membrane containing the high-precision filtration layer.

[0079] 4. Preparation of adsorption layer by spraying

[0080] (1) Pretreatment of 2# zeolite: 6 parts of hydroxypropyl methylcellulose and water are mixed into an aqueous solution at a mass ratio of 1:30, and then 60 parts of 2# zeolite are added and stirred for 3 hours. After the pores on the surface of the 2# zeolite particles completely adsorb the hydroxypropyl methylcellulose aqueous solution, the granulation is spray-dried at 110°C to obtain prefabricated 2# zeolite for standby use;

[0081] (2) 55 parts of prefabricated 2# zeolite, 5 parts of anhydrous ethanol, 6 parts of sodium carboxymethyl cellulose, 4 parts of hydroxypropyl methylcellulose, 7 parts of polyvinyl alcohol aqueous solution and 23 parts of water were mixed, added to a planetary ball mill and mixed for 2 hours, and centrifuged for 60 minutes to obtain an adsorption layer slurry;

[0082] (3) The adsorption layer slurry is uniformly sprayed on the surface of the flat membrane support at a positive pressure of 0.03 MPa, with a spraying thickness of 400~500 μm, and then rapidly radiated dried at 90°C until the water loss rate is ≥96%, and then heated from 30°C to 120°C at a rate of 30°C / h; then heated to 450°C at a rate of 120°C / h, and sintered for 2 hours to obtain a ceramic flat membrane containing an adsorption layer.

[0083] 5. Filling and strengthening adsorbent and end packaging

[0084] (1) Single-end ABS strip packaging: Use epoxy resin to seal one end of the ceramic flat membrane containing the adsorption layer with an ABS strip, and then naturally dry and solidify it for 24 hours;

[0085] (2) Filling method: Place the single-head packaged flat membrane with the opening facing upwards, and fill 50 parts of 3# zeolite and 50 parts of activated carbon powder particles into the pores of the flat membrane. Vibrate and fill appropriately to enhance the filling of the adsorbent.

[0086] (3) Encapsulating the other end with ABS rubber strip: According to the above step (2), seal the end with BS rubber strip. After natural drying and curing for 24 hours, a high-flux and high-precision ceramic flat membrane product is obtained.

[0087] Comparative Example 1

[0088] 1. Preparation of Ceramic Flat Membrane Mud Body

[0089] 50 parts of silicon carbide, 5 parts of high-boron ultrafine glass powder and 5 parts of kaolin were added into Elysee high-speed mixer and premixed at 1000r / min for 15 minutes, then 10 parts of hydroxypropyl methyl fiber, 5 parts of tung oil, 5 parts of polyvinyl alcohol aqueous solution and 15 parts of water were added and mixed for 20 minutes, finally 5 parts of pore-forming agent PP hollow balls were added and mixed evenly at 600r / min for 10 minutes, after mixing, they were added into mud kneading machine for vacuum-0.085MPa mud kneading, and after mud kneading, they were put into aging box for aging at temperature of 24~28℃ and humidity of 80~85%, and after aging, they were extruded into ceramic flat membrane mud body at vacuum-0.090MPa and pressure of 6.1~6.3Mpa; the rest of the preparation steps and parameters were the same as those in Example 1 to obtain a ceramic flat membrane.

[0090] Comparative Example 2

[0091] When preparing the ceramic flat membrane, ABS strip packaging was directly performed without using the filling method to fill the adsorbent. The remaining preparation steps and parameters were the same as those in Example 1 to obtain the ceramic flat membrane.

[0092] Comparative Example 3

[0093] When preparing the ceramic flat membrane, only 100 parts of activated carbon powder particles were filled into the pores of the flat membrane, and no 3# zeolite was added. Vibration filling was used as an enhanced filling adsorbent. The remaining preparation steps and parameters were the same as in Example 2 to obtain a ceramic flat membrane.

[0094] Comparative Example 4

[0095] When preparing the ceramic flat membrane, only 100 parts of 3# zeolite were filled into the pores of the flat membrane and vibrated to form an enhanced filling adsorbent. The remaining preparation steps and parameters were the same as those in Example 2 to obtain a ceramic flat membrane.

[0096] Comparative Example 5

[0097] When preparing the ceramic flat membrane, the 2# zeolite in the adsorption membrane raw material was not pretreated when the adsorption layer was prepared by the spraying method. The remaining preparation steps and parameters were the same as those in Example 2 to obtain a ceramic flat membrane.

[0098] Example 3

[0099] The ceramic flat membranes prepared in Examples 1-2 and Comparative Examples 1-4 were subjected to performance characterization tests, and the results are shown in Table 2. The present invention uses a bubble pressure method to determine the pore size of the membrane layer; a spectrophotometer to determine the iron removal rate; a scattered light method to determine the turbidity; and a suction method to determine the pure water flux.

[0100] Table 2 Performance test results of ceramic flat membranes prepared in Examples 1-2 and Comparative Examples 1-4

[0101]

[0102] It can be seen from Table 2 that compared with Comparative Example 1, after the zeolite component is introduced into the support, Example 1 has a significantly higher iron removal rate than Comparative Example 1, and the turbidity is significantly better than Comparative Example 1; compared with Comparative Example 2, Example 2 does not perform enhanced adsorbent filling, and the iron removal rate is significantly worse than that of Example 1; Example 2 is compared with Comparative Example 3 and Comparative Example 4 in terms of the mixed use of enhanced adsorbent types and a single variety, and the enhanced adsorption effect of the mixed zeolite molecular sieve and activated carbon is worse than that of a single variety of adsorbent; In the process of preparing the adsorption layer of Example 2 and Comparative Example 5, the effects of pre-treatment and sealing of 2# zeolite in the adsorption membrane raw material on subsequent performance are compared. By comparison, it can be seen that the iron removal rate and effluent turbidity of Example 2 after pre-treatment and sealing of 2# zeolite are significantly better than those of Comparative Example 5 without treatment.

[0103] Through a large number of experiments not limited to the above, after optimizing the formula raw materials, calculating and matching the formula system, optimizing the component reorganization, and combining the unique drying and firing indicators in the later stage, a filtration adsorption membrane plate combining organic adsorbent, inorganic adsorbent and inorganic ceramic membrane was obtained.

[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-flux, high-precision ceramic flat membrane for removing the iron odor of drinking tap water, characterized in that: It includes a support body, a high-precision filter layer, an adsorption layer and a filling adsorbent; The support comprises the following raw materials and their weight proportions: 20-50 parts of silicon carbide, 15-20 parts of prefabricated 1# zeolite, 2-5 parts of high-boron ultrafine glass powder, 3-6 parts of kaolin, 4-8 parts of PP balls, 5-12 parts of hydroxypropyl methylcellulose, 4-6 parts of tung oil, 3-6 parts of polyvinyl alcohol aqueous solution, and 12-18 parts of water; The high-precision filter layer includes the following raw materials and their weight fractions: 40-46 parts of titanium dioxide, 0.02-0.1 parts of polyacrylamide, 1-3 parts of anhydrous ethanol, 5-10 parts of polyacrylic acid, 7-18 parts of polyvinyl alcohol aqueous solution, and 25-40 parts of water; The adsorption layer comprises the following raw materials and their weight proportions: 30-55 parts of prefabricated 2# zeolite, 3-5 parts of anhydrous ethanol, 5-10 parts of sodium carboxymethyl cellulose, 3-6 parts of hydroxypropyl methyl cellulose, 5-12 parts of polyvinyl alcohol aqueous solution, and 20-35 parts of water; The filling adsorbent includes the following raw materials and their mass proportions: 45-55 parts of 3# zeolite and 45-55 parts of activated carbon powder.

2. A method for preparing the high-flux, high-precision ceramic flat membrane for removing the iron odor of drinking tap water according to claim 1, characterized in that: The following steps are involved: 1) Preparation of ceramic flat membrane mud body: After a certain ratio of silicon carbide, prefabricated 1# zeolite, ultrafine glass powder and kaolin are mixed at high speed, hydroxypropyl methylcellulose, tung oil, polyvinyl alcohol aqueous solution and water are added and mixed evenly, and finally pore-forming agent PP balls are added and mixed evenly at a slow speed, after the mixing is completed, the mixture is added to a mud kneading machine for mud kneading, and after the mud kneading, the mixture is placed in an aging box for aging, and after aging, it is extruded and formed into a ceramic flat membrane mud body; 2) Preparation of ceramic flat membrane support; 3) Preparation of high-precision filter layer by dip coating: The ceramic flat membrane support body is clamped at both ends with a clamp, with the side as the upper and lower sides, and is evenly immersed and suspended in the high-precision filter layer slurry, and vacuum -0.04~-0.06MPa adsorption is performed, the adsorption time is 5~10s, and the adsorption thickness is 100~180μm. After drying, it is sintered at 650~750℃ to obtain a ceramic flat membrane containing a high-precision filter layer; 4) Preparation of adsorption layer by spraying method: The adsorption layer slurry is uniformly sprayed on the surface of the ceramic flat membrane containing the high-precision filtration layer with a thickness of 200-500 μm, and then quickly dried at 80-90°C, and then sintered at 350-500°C to obtain the ceramic flat membrane containing the adsorption layer; 5) Filling and strengthening adsorbent and end packaging.

3. The method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron smell of drinking tap water according to claim 2, characterized in that: The preparation process of the prefabricated 1# zeolite is as follows: hydroxypropyl methylcellulose and water are prepared into an aqueous solution at a mass ratio of 1:30, 1# zeolite is added, stirred and soaked for 2-4 hours, and the pores on the surface of the zeolite particles completely adsorb the hydroxypropyl methylcellulose aqueous solution, and then spray-dried and granulated at 110° C. to obtain the prefabricated 1# zeolite.

4. The method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron smell of drinking tap water according to claim 2, characterized in that: In the step 2), the process of preparing the ceramic flat membrane support body is as follows: the formed ceramic flat membrane mud body is naturally moisturized and dried for 48 to 55 hours, and then subjected to heating radiation drying at a temperature of 60 to 90° C. for a drying time of 4 to 15 hours. After drying the body, it is sintered to obtain the ceramic flat membrane support body.

5. The method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron odor of drinking tap water according to claim 4, characterized in that: The specific sintering process of the dried green body is: heating the dried green body from 30°C to 400°C at a rate of 60°C / h, then heating it to 800-850°C at a rate of 100°C / h, and keeping it warm for 1-3.5h.

6. The method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron odor of drinking tap water according to claim 2, characterized in that: In the step 3), the preparation process of the high-precision filter layer is as follows: titanium dioxide, polyacrylamide, anhydrous ethanol, polyacrylic acid, polyvinyl alcohol aqueous solution, and water are added to a ball mill and mixed for 7 to 15 hours, ultrasonically treated for 1 to 2 hours, and then added to a ball mill and mixed for 1 to 3 hours to obtain a high-precision filter layer slurry.

7. The method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron odor of drinking tap water according to claim 2, characterized in that: In the step 3), the specific sintering process is: the temperature is raised from 30°C to 300°C at a rate of 30°C / h; then raised to 650-750°C at a rate of 60°C / h, and sintered for 1-2 hours to obtain a ceramic flat membrane containing a high-precision filter layer.

8. The method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron odor of drinking tap water according to claim 2, characterized in that: In step 4), the preparation steps of the adsorption layer slurry are as follows: (1) After preparing an aqueous solution of hydroxypropyl methylcellulose and water in a mass ratio of 1:30, add 2# zeolite and stir and soak for 2-4 hours. After the pores on the surface of the zeolite particles completely adsorb the hydroxypropyl methylcellulose aqueous solution, spray dry and granulate at 110°C to obtain prefabricated 2# zeolite; (2) Prefabricated 2# zeolite, anhydrous ethanol, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl alcohol aqueous solution and water are mixed, added into a planetary ball mill and mixed for 1 to 2 hours, and then centrifuged and dispersed for 30 to 60 minutes to obtain an adsorption layer slurry.

9. The method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron odor of drinking tap water according to claim 2, characterized in that: In the step 4), the specific process of sintering is: heating the dried ceramic flat membrane containing the adsorption layer from 30°C to 120°C at a rate of 30°C / h, then heating to 350-500°C at a rate of 120°C / h, and keeping the temperature for 1-3h.

10. The method for preparing a high-flux, high-precision ceramic flat membrane for removing the iron odor of drinking tap water according to claim 2, characterized in that: In the step 5), filling the enhanced adsorbent and the end cap packaging specifically include the following steps: S1. One end of the ceramic flat membrane containing the adsorption layer is sealed with an ABS strip using epoxy resin, and then naturally dried and cured for 24 hours; S2. The opening of the single-head packaged ceramic flat membrane is vertically facing upward, and 3# zeolite and activated carbon powder particles are filled into the pores of the flat membrane, and vibrated to fill them as enhanced filling adsorbents; S3.: According to step S1, encapsulate the other end of the ABS strip, dry and cure naturally for 24 hours, and finally obtain a high-flux and high-precision ceramic flat membrane.

Citation Information

Cited By

  • Ceramic flat sheet membrane and end seal integrated co-firing molding process

    CN120943667A